The Role of the Hidayatullah Tahfidz Foundation in the Religious Social Life of the Kukup Village Community in Koya Koso, Jayapura City - Indra Rizki; Muh. Syukri Nawir; Muhammad Taslim (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
The low awareness in community life both in terms of social interaction and in the religious behavior of the people of Kukup Village, Koya Koso has become a common concern in the social environment of people who want good in this world and the hereafter. In general, this study aims to describe the portrait of the socio-religious life of the people of Kukup Village, Koya Koso and describe the role of the Tahfidz Hidayatullah Foundation in the religious social life of the people of Kukup Village, in Koya Koso, Jayapura City. This research used a descriptive qualitative approach with data collection methods through observation, in-depth interviews, and documentation. The subjects of the study included community leaders, guardians of students, traders, mosque administrators and foundation administrators who were all members of the people of Kukup Village, Koya Koso. The results of the study show that the social life of the people of Kampung Kukup, Koya Koso is a life full of busyness from economic activities and in religious life, such as religious behavior is a difficult thing to carry out as a command of God, so in order to compensate for this busyness, the Hidayatullah Tahfidz Foundation has created a program as a role that can be taken such as: Rumah Qur'an Hidayatullah or Hidayatullah Qur'an House (RQH) for children and Majelis Qur'an Hidayatullah or Qur'an Assembly Hidayatullah (MQH) for the community and Raudhatul Athfal (RA) as a level of formal education, which is a forum for the community to carry out the educational process by sharing and learning with each other in order to become a good Muslim person.